中国儿童汉语句末语气词获得研究 (Acquisition Of Sentence-Final Particles Among Chinese Speaking Children In China) - Zhang, Di (2019)
As a form of Chinese language, modal particles are commonly used in modern Chinese. In the second language acquisition, that is, the teaching of Chinese as a second language, it is more difficult for foreign students to acquire such words. However, in the acquisition of children’s language, they can acquire modal particles in just over a year. How do they acquire and feel so sensitive to the mood? This deserves our in-depth study. The study of this thesis intends to build the “Chinese Children’s Sentence Final Particles Corpus” as a sub-corpus based on “the Chinese Children’s Multi-modal Oral Corpus” . With a long-term tracking of four children’s linguistic data for the past three years, the study has integrated Universal Grammar Theory, Cognitive Development Theory, Systemic Functional Linguistics and Speech Act Theory in order to solve the theoretical and pragmatic problems in the acquisition of children’s sentence-final particles with a combination of quantitative and qualitative methods. The purpose of the research is to generalize the rules, dominant factor, growth patterns, verbal intentions and construct a pragmatic function network based on the v analysis of data about children’s sentence-final particles.The thesis divides modal particles into typical modal particles (tone particles and functional modal particles) and general modal particles in order to get an overall view of the sentence-final particles’ acquisition in Chinese-speaking children. From the perspective of the pragmatic use of typical sentence-final partcles, this thesis first examines the appearance of sentence-final particles from the aspect of sentence types. Speech intentions of the typical sentence-final particles are extracted and combined with sentence patterns for further generalizations of pragmatic functions to draw the core sematic map or prototype meaning, therefore to analyze the operation mechanism by constructing a pragmatic function network of sentence-final particles. In this thesis, it has been found that the acquisition order of children’s sentence-final particles is a, ba, ne, la＞ma（吗）, de, le2 ＞lou, ma（嘛） （“>” means earlier than）; the acquisition pattern is tone particles> functional modal particles>general modal particles; the dominant component affecting the overall internal language development is the functional modal particle; the earlier the distribution of sentence types becomes dominant, the sooner it is obtained. It also has been found that, on the premise of sentence types acquisition, the higher the core pragmatic level is, the earlier it would be obtained. From the tone level of the typical sentence-final particles, it has been found that the sentence-final particles vi at the end of two levels are obtained first and then obtained in order of rank from two ends towards the middle. The core semantics is found consist of subjectivity and interactive subjectivity, and a positive correlation has been found between the two. The pragmatic system of the typical sentence-final particles are found be composed of three levels: core semantics, pragmatic functions and speech intentions. This thesis clarifies the role of different factors in the acquisition of children’s sentence-final particles. First of all, the abstract classification structure and the predominant factor of modal particles are children’s inherent and intrinsic linguistic knowledge. The influence of the surrounding speech input does not predominate. In addition, a correlation has been found between parents’ input and children’s acquisition of sentence-final particles, but with low significance. What’s more, it also has been found that the more dominant a typical sentence-final particle distributed in sentence types, the earlier they are obtained, and the acquisition order of the core pragmatic level is constrained by the distribution of sentence types which also belongs to children’s linguistic knowledge. This kind of knowledge limits the acquisition order of the core pragmatic level.